Bone marrow mesenchymal stem cells could reduce the toxic effects of hexavalent chromium on the liver by decreasing endoplasmic reticulum stress-mediated apoptosis via SIRT1/HIF-1α signaling pathway in rats. (August 2019) - Zhao, Yue; Yan, Jun; Li, An-Pei; Zhang, Zhi-Li; Li, Zhong-Run; Guo, Ke-Jun; Zhao, Kun-Chi; Ruan, Qing; Guo, Li
Highlights: The hexavalent chromium can accumulate in rat liver and can cause liver damage. BMSCs transplantation can reduce the toxic effects of hexavalent chromium on livers. The mechanism is that BMSCs could decrease the apoptosis of hepatocyte mediated by ER stress via the SIRT1/HIF-1a pathway. Abstract: This study focused on the effect of bone marrow mesenchymal stem cells (BMSCs) on the repair of rat liver injury induced by Cr (VI). Twenty-four Wistar rats were randomly divided into the control, model and cell therapy group, with 8 rats in each group. Potassium dichromate solution containing 0, 0.4 and 0.4 mg/kg·bw Cr (VI) was administered 5 times a week for 30 days. At the end of treatment, rats in the cell therapy group were administered 1 × 10 7 BMSCs. Two weeks later, serum alanine and aspartate aminotransferase levels in the cell therapy group were significantly improved compared with those in the model group, CM-Dil-labeled BMSCs were localized in rat livers. Compared with the model group, in the cell therapy group the number of apoptotic hepatocytes by TUNEL assay, MDA content, the expression of HIF-1α, endoplasmic reticulum (ER) stress-mediated apoptosis-related proteins including Grp78, CHOP, Cleaved-Caspase-12, ATF6, and Bax was significantly lower, and SOD activity, the expression of SIRT1 and Bcl-2 was significantly higher. It is suggested that BMSCs are localized in livers and reduce the toxic effects of Cr (VI) on the liver, and the possible mechanism may be related to the mechanisms of BMSCs decreasing ER stress-mediated hepatocyte apoptosis via the SIRT1/HIF-1α signaling pathway.